Development of Integrated Strategy for Managing Construction Sector in Iraq Project Management Maturity Models - Ibrahim A. Mohammad; Faiq M. Sarhan Al-Zwainy; Saja H. Raheem (Engineering and Technology Journal, 2016)
A lot of construction projects fail to complete their processes according plans, leading to financial and technical problems. The paper tries to study the extent to which the application of best management practices will have a quantitative measurable effect on project success. The researcher developed a model to assess project management maturity for a sample study of the Iraqi ministry of construction and housing and public municipalities, then applied regression analysis to find the correlation of the maturity level of the cost, time management and the average project management processes maturity level and also deviation coefficient during the year (2007-2014).